Using programme theory to assess the feasibility of delivering micronutrient Sprinkles through a food-assisted maternal and child health and nutrition programme in rural Haiti - Loechl, Cornelia U.; Menon, Purnima; Arimond, Mary; Ruel, Marie T.; Pelto, Gretel H.; Habicht, Jean-Pierre; Michaud, Lesly (Wiley, 2009)
This paper uses programme theory to assess, in the context of an effectiveness evaluation, the feasibility and acceptability of distributing micronutrient Sprinkles through a food‐assisted maternal and child health and nutrition programme in rural Haiti. We laid out the steps related to programme delivery and household utilization of Sprinkles and used qualitative and quantitative methods to gather data on these steps. Methods included structured observations, checks of beneficiary ration cards, exit interviews, focus group discussions (FGD), individual interviews and survey data from the effectiveness evaluation. Results are as follows: (1) information on use of Sprinkles was provided before mothers first received them, as planned; (2) Sprinkles were re‐packaged and distributed as planned and in the appropriate amount; (3) almost all mothers (96%) received two monthly rations of Sprinkles and received timely information on their use; (4) mothers understood instructions about use of Sprinkles and acceptance was high, and no selling of the product was reported or observed; and (5) mothers reported using Sprinkles as instructed, every day (63% in survey; 86% at exit interviews), and for the child only (99%). FGD with staff highlighted the acceptance of the intervention, with a reported ‘modest’ increase in workload. Within this well‐established programme, it proved feasible to distribute Sprinkles and to ensure appropriate use by beneficiary mothers. Existing programme venues were suitable for distributing Sprinkles and educating mothers about their use. Use of programme theory helped to assess feasibility and acceptability of the Sprinkles intervention and provided useful information for programme replication or scale‐up.